Using Photo-ID to document and monitor the prevalence of fibropapilloma tumours in a foraging aggregation of green turtles - Hancock, Joana M.; Choma, Jenni; Mainye, Leah; Wambi, Paul; Stelfox, Martin R.; Polyak, Maximilian M. R.; Wambua, Sammy; Köhnk, Stephanie (Frontiers in Marine Science, 2023)
Sea turtle in-water monitoring has been conducted in Diani-Chale National Marine Reserve (DCMR) in Kenya’s South Coast since 2018, where green sea turtles (Chelonia mydas) may be found resting or foraging. Underwater surveys are conducted at a regular basis to collect data on sea turtle occurrence, abundance, and distribution, incorporating photographic identification (Photo-ID) as a capture-mark-recapture method. Photo-ID is a non-invasive, low-cost, citizen-science-friendly approach that allows researchers to obtain discrete information about individuals’ locations and health status at a given time, which is essential knowledge for spatial planning and conservation management of endangered species. When visible in the photos collected on a single individual, the occurrence of external tumours is noted, and the turtle is flagged for fibropapilloma (FP) monitoring. From July 2018 to December 2022, 2757 green turtle encounters were recorded, resulting in the identification of 571 individuals. External tumours were observed in 75 individuals. The temporal progression of the tumour’s growth was monitored through subsequent re-sightings of 47 of the affected individuals, with evidence of tumour progression and regression. Documenting the incidence of this disease on sea turtles usually involves the manipulation of captured animals, and is quite possibly under-documented in foraging grounds. Tracking the evolution of this disease using Photo-ID can be a useful, non-invasive method to understand its extent in foraging aggregations where turtles can be easily observed underwater.